The electrochemistry of quinizarin revealed through its mediated reduction of oxygen. - Batchelor-McAuley, C; Dimov, I; Aldous, L; Compton, R (2011)
After 35 years the hunt for improved anthracycline antibiotics is unabated but has yet to achieve the levels of clinical success desired. Electrochemical techniques provide a large amount of kinetic and thermodynamic information, but the use of such procedures is hindered by issues of sensitivity and selectivity. This work demonstrates how by harnessing the mechanism of catalytic reduction of oxygen by the quinone functionality present within the anthracycline structure it is possible to study the reactive moiety in nanomolar concentration. This methodology allows electrochemical investigation of the intercalation of quinizarin into DNA and, in particular, the quinone oxidation and degradation mechanism. The reversible reduction of the quinizarin, which in the presence of oxygen leads to the formation of reactive oxygen species, is found to occur at -0.535 V (vs. SCE) pH 6.84 and the irreversible oxidation leading to the molecules degradation occurs at +0.386 V (vs. SCE) pH 6.84.